Education, Learning, Training - Carbonnier, G.; Carton, M.; King, K. (Brill, 2014)
In Education, Learning, Training: Critical Issues for Development, renowned scholars and practitioners examine shifts in global education policy and practice over the last 50 years.
English
Keywords: Development studies; international development; Africa; Capability approach; China; Higher education; Lifelong learning; Massive open online course